Spinoza and Spinozism in the Western Enlightenment: the Latest Turns in the Controversy - Israel, Jonathan (Araucaria, 2024)
This article seeks to outline the main elements in the historiographicalcontroversy over the significance of 'Spinozism' as an eighteenth-centuryEnlightenment category and the validity or otherwise of the concept of 'RadicalEnlightenment' as well as the relationship between these two categories. Defining'Radical Enlightenment' as the philosophical rejection of religious authoritycombined with a democratic tending system of social and political thought,and as a partly clandestine tradition that evolved in opposition to the moderatemainstream Enlightenment, it seeks to sketch in the main features both of the'negative critique' broadly opposing this way of understanding the WesternEnlightenment and the 'positive critique' that accepts this classification in broadoutline.